An annotated catalog of Evanioidea (Insecta: Hymenoptera) from China - Li, Yicheng; He, Yanbiao; Chen, Huayan (Zootaxa, 2024)
The taxonomy of the superfamily Evanioidea from China has long been neglected, and the current status of their classification inhibits further research on their biology. This catalog updates and documents the genus- and species-level taxonomy for both extant and extinct species of the superfamily Evanioidea recorded from China, while providing information on type depositories and distributional data. Results from an extensive review of literatures, including host records and taxonomic notes, are also provided. A total of 84 extant (plus 59 fossil) species and 7 extant (plus 17 fossil) genera within six families of Evanioidea (Insecta: Hymenoptera) from China are recognized as valid.